ANALYSIS OF SPEECH ACTS IN COMIC ''AVATAR THE LAST AIRBENDER: SMOKE AND SHADOW'' - Made Suci; I GB Wahyu Nugraha Putra; Ni Nyoman Deni Ariyaningsih (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
Speech acts was a set of things we do when we speak and in performance an action through an utterances. Speech act not only found in daily conversation but also in literary work such as: Movie, novel and comic. This study concern with speech acts produced by the main character in comic. The aims of this study was to finding out the kind of speech act produced by Zuko as the main character in Avatar the Last Airbender: Smoke and Shadow comic. The data in this study was taken from the utterances of the main character and used theory of Speech acts proposed by Yule (1996) to analysing the kind of speech act. In collecting the data, observation method was applied in this study. The data was analysing used Descriptive qualitative method. In presenting the conclusion, formal and informal method was used in table and description form by using sentences. The finding of this study shows that, there were 20 data and four types of speech act found in Zuko utterances. Those four type of speech acts consist of 6 (30%) data of Representatives, 5 (25%) data of Expressive, 7 (35%) data of Directive, and 2 (10%) data of Commissive. Among the data, the most dominant of speech act found in Zuko utterances was Directive in making a command, because in the story he was the lord of fire nation which have role to commanding his subordinate to do something.